Towards a Self-powered Biosensors for Environmental Applications in Remote, Off-grid Areas. (2017) - Pasternak, Grzegorz; Greenman, John; Ieropoulos, Ioannis
Abstract: One important factor for developing biosensors is taking the source of electrical energy into account. The source of electricity is needed whenever we consider point-of-care diagnostics, in-vivo tests or in particular – environmental applications. The need of supplying energy to biosensor may be an important obstacle for its everyday use, particularly in developing countries. Here, we present the concept of biosensor able to generate power by bioelectrochemical oxidation of the analyte and thus – able to autonomously maintain its operation.